The Role of the Principal's Academic Supervision in Optimizing the Implementation of the Independent Curriculum - Desy Eka Citra Dewi; Nurniswah; Nurhikmah; Elfahmi Lubis (Jurnal Teknologi Pendidikan)
This research aims to 1) describe and analyze the form of academic supervision of school principals in implementing the independent curriculum in Bengkulu City Public Middle Schools and 2) to describe and analyze the implementation of the independent curriculum in Bengkulu City Public Middle Schools. This type of research is combination research (Mix Method) with a Sequential Explanatory Design model approach. The research population and sample used purposive sampling techniques, data collection techniques: observation, questionnaires, interviews and documentation. Data that has been collected in the form of a questionnaire will be scored and analyzed using descriptive statistics, namely using the percentage formula (%), Qualitative data collection techniques are observation, interviews and documentation. Qualitatively the data was analyzed using the Miles and Huberman model. The results of the research are the form of academic supervision of school principals in implementing the independent curriculum in state junior high schools in Bengkulu City, namely: 1. The principal helps improve teacher professionalism, by: a. help improve teachers' academic understanding of the independent curriculum, b. help teachers design teaching modules, 2. The principal supervises the implementation of independent curriculum learning by: a. the principal visits the class while the teacher is teaching, b. the principal observes the teacher's readiness in teaching, c. the principal holds discussions with teachers and d. The principal helps teachers how to utilize learning resources in the classroom. 3. The school principal supervises learning outcomes evaluation activities in the form of diagnostic evaluations, formative evaluations, summative evaluations and school exams.